Abundanceand Diversity of the Types of Gastropoda Based on Density of SeagrassinJago Jago Village CentralTapanuli - Mardiono Rajagukguk; Zulkifli Zulkifli; Afrizal Tanjung (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Gastropoda is one class of molluscs known to be well associated with seagrass ecosystems. Gastropods that live with seagrass have a high diversity and abundance compared to habitats that are not covered with seagrass. The purpose of this study was to determine the density level of seagrass, abundance and diversity of gastropod species associated with seagrass and to know the relationship of gastropod abundance to the density level of seagrass in the waters of Jago Jago Village, Central Tapanuli. The research was carried out in April - May 2019. From the results of the study it was found that seagrass density in areas without human activity was 44.33 stands/m2 followed by tourist areas of 24.22 stands/m2 then in residential areas it was 20.89 stands/m2. Gastropod abundance in areas without human activity is equal to 20.70 ind/m2, then gastropod abundance in tourist areas is 14.19 ind/m2 and gastropod abundance in residential areas is equal to 10.33 ind/m2. The diversity of gastropods in residential areas is 1.45, followed by regions without human activity, namely 1.10 and gastropod diversity in tourist areas, which is 0.96. The results of a simple linear regression test of the relationship between seagrass density and gastropod abundance obtained positive results, namely r = 0.947Keywords: Gastropod, seagrass, density of seagras, abundance of gastropod, diversity of gastropod.